2017
DOI: 10.1111/jan.13511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight stigma on physiological and psychological health outcomes for overweight and obese adults: A systematic review

Abstract: Weight stigma is associated with adverse physiological and psychological outcomes. This conclusion highlights the need to increase public and professional awareness about the issue of weight stigma and the importance of the further development of assessment and prevention strategies of weight stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
271
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(295 citation statements)
references
References 47 publications
8
271
2
14
Order By: Relevance
“…Weight stigma, rather than obesity itself, may be particularly harmful to mental health and is associated with depressive symptoms, higher anxiety levels, lower self-esteem, social isolation, perceived stress, substance use [24][25][26] , unhealthy eating and weightcontrol behaviors, such as binge eating and emotional overeating 27 . Experimental studies also show, paradoxically, that exposing individuals to weight stigma can lead to increased food intake, regardless of BMI 3,28 .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Weight stigma, rather than obesity itself, may be particularly harmful to mental health and is associated with depressive symptoms, higher anxiety levels, lower self-esteem, social isolation, perceived stress, substance use [24][25][26] , unhealthy eating and weightcontrol behaviors, such as binge eating and emotional overeating 27 . Experimental studies also show, paradoxically, that exposing individuals to weight stigma can lead to increased food intake, regardless of BMI 3,28 .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Because obesity is such a highly stigmatized condition, people with higher weight are vulnerable to weight‐based prejudice, victimization and discrimination . These experiences contribute to harmful health consequences for targets of weight stigma and can impair both psychological wellbeing and physical health . Studies further indicate that healthcare providers' use of stigmatizing communication about body weight can exacerbate this problem in the medical setting and undermine delivery of health care for patients with high body weight .…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have shown that experiencing weight stigma predicts weight gain and obesity over time, controlling for demographic characteristics and baseline body weight (15). Research has suggested that weight stigma contributes to weight gain through a range of behavioral and psychological mechanisms, such as maladaptive eating behaviors like binge eating and unhealthy weight control practices (16), increased physiological stress (17), and poor psychological health (18). This evidence demonstrates weight stigma Original Article EPIDEMIOLOGY/GENETICS to be a key psychosocial contributor to obesity and poor weightrelated health (19).…”
Section: Introductionmentioning
confidence: 99%